Arthroscopic Side-to-Side Repair of Massive Rotator Cuff Tears Maintains Adequate Functional Improvement at 12 to 14 Years' Follow-up. Issue 2 (February 2021) - Merlet, Marie Caroline; Guinet, Virginie; Rousseau, Thomas; van Rooij, Floris; Saffarini, Mo; Dujardin, Franck; Courage, Olivier
Background: Rotator cuff tears are common shoulder injuries that often cause pain and loss of function. Nonanatomic side-to-side techniques facilitate repair by minimizing tensions within tendons to improve healing and optimize the thickness of sutured tissues. Purpose/Hypothesis: The purpose was to evaluate long-term clinical and radiographic outcomes of arthroscopic side-to-side repair of massive rotator cuff tears (mRCTs). The hypothesis was that, at a minimum follow-up of 12 years, arthroscopic side-to-side repair maintains clinically important improvements. Study Design: Case series; Level of evidence, 4. Methods: The authors reviewed records of all patients who underwent arthroscopic repair of mRCTs over 2 consecutive years. A total of 30 adult patients met the eligibility criteria and underwent side-to-side repair. Patients were evaluated clinically using the Constant score (CS) and ultrasound to assess retears at 3 timepoints after surgery: 2 to 4 years, 5 to 7 years, and 12 to 14 years. Results: At first follow-up (3.2 ± 0.5 years), all 30 patients had clinical and ultrasound assessment, which revealed 13 retears (43%). At second follow-up (6.2 ± 0.5 years), all 30 patients had clinical and ultrasound assessment, which revealed 2 new retears (total 50%). At final follow-up (13.0 ± 0.7 years), only 21 patients had clinical assessment (1 died and 8 could not be reached), and only 19 patients had ultrasound assessment, which revealed 6 new retears (total 79%). Both absolute CS and age-/sex-adjusted CS improved significantly from baseline values at first follow-up (73.5 and 96.6, respectively), and remained stable at second follow-up (69.0 and 91.9, respectively), and final follow-up (64.4 and 87.0, respectively). Compared to shoulders with intact repairs, those with retears tended to have lower absolute CS at all follow-up visits, although differences were not statistically significant. Conclusion: Patients with mRCTs maintain satisfactory clinical scores at 12 to 14 years after arthroscopic side-to-side repair despite a high incidence of retears. Repair is a safe and effective treatment for mRCTs, providing a less invasive and less complex alternative to reverse shoulder arthroplasty and tendon transfer procedures.